PENGARUH CORPORATE GOVERNANCE DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - YULIANI ALMALITA (Jurnal Bisnis dan Akuntansi, 2017)
The objective (s) of this research was verifying whether good corporate governance (size of audit committee, proportion of independent commissioner, institutional, managerial ownership, size of commissioner) leverage, free cash flow, profitability, losses, audit quality and market to book on earnings management and company’s size as control variable. Data analyze used in this research is secondary data and using purposive sampling where total sample are 69 listed companies on manufacture sector for period 2012-2013. Analysis data method that used in this research is multiple regression method with using SPSS version 19.0. The result of the research concludes that leverage and market to book have influence to earnings management. Whereas size of audit committee, proportion of independent commissioner, institutional, managerial ownership, size of commissioner, free cash flow, profitability, losses,